Peningkatan Keterampilan Bermain Bola Basket melalui Pelatihan Teknik Dasar bagi Mahasiswa Pendidikan Jasmani - Erwin S. Neolaka; Ratno Susanto; Jurdan Martin Siahaan (PT. Penerbit Riset Sadwa, 2026)
Basic basketball technical skills are a must-have competency for Physical Education, Health, and Recreation students at the Faculty of Teacher Training and Education, Nusa Cendana University, as a foundation for learning, sports coaching, and coaching. However, students still experience difficulties in mastering basic techniques such as dribbling, passing, shooting, and pivoting due to limited training intensity and a lack of structured mentoring. This Community Service (PkM) activity aims to improve basketball playing skills through basic technical training for Physical Education students. The implementation method includes preparation, identification of participant needs, material delivery, technical demonstrations, step-by-step practice, game simulations, mentoring, and evaluation of participant abilities. The training was conducted using a participatory approach with an emphasis on direct practice, feedback, and repeated practice so that participants can master basic movements effectively. Evaluation was carried out through observation of technical skills, participant activity, and assessment of abilities before and after training. The results of the activity showed an increase in participants' ability to perform basic basketball techniques, an increased understanding of game principles, and a growing motivation to practice independently. In addition, participants showed increased confidence in applying skills in simple game situations. This program has had a positive impact on improving the competency of Physical Education students as future educators and sports coaches. Therefore, training in basic basketball techniques can be an effective coaching model for improving the quality of sports practice in higher education settings.